The effect of capital structure, and growth on firm value on real estate and property companies listed on BEI (2015-2019 period) - Trio Nugroho; Dina Patrisia (Financial Management Studies, 2022)
The value of the company is a benchmark for investors to invest. For this reason, the value of the company is an important factor that must be increased by every company, because investors will tend to invest their shares in companies that have a high value. The focus of this research is to explain the influence of capital structure and growth on firm value. The research sample consisted of taken from 36 companies with five years of observation. The total sample consisted of 156 observation samples after undergoing data screening. . The analysis technique in this research is multiple linear and non-linear regression analysis. The results of this study indicate that the capital structure based on market value measurement (MLLEV) on linear and non-linear regression has a negative and significant effect. The capital structure based on the measurement of book value (LTDTA) in the non-linear model has a positive and significant effect, but has no influence on the linear model. Growth has no effect on firm value in all models.